(untitled) (Eastern Librarian, 2012)
This paper presents and analyses the status of electronic resources facilities and services provided by the Dhaka University Library (DUL). It also discusses the purpose of using e-resources, benefits, subject coverage status, overall user satisfactions, problems that are faced by DUL users while accessing e-resources and perceived impact of e-resources on users. Finally, it reports the results from questionnaire-based survey of e-resources use and its impact on DUL users. DOI: http://dx.doi.org/10.3329/el.v23i1.12122 Eastern Librarian Vol.23(1) 2012 pp.74-90